A good girl's guide to murder - Jackson, Holly, 1992- (Jackson, Holly, 1992- Good girl's guide to murder novel, 2020)
As her senior capstone project, Pippa Fitz-Amobi is determined to find the real killer in a closed, local murder case, but not everyone wants her meddling in the past--Publisher's description.